EFFECTS OF ECCENTRIC LOAD ON PLAIN AND CFRP LAMINATED REINFORCED CONCRETE BEAM - ,, MUHAMMAD IMRAN (2014)
Beams as structural members are sometimes subjected to a variety of combined stresses due to unsymmetric loads. This unsymmetric loads on beams in a building structures are caused by the combination of non-uniform loading such as unequal span, large cantilever slabs, uneven structure configuration, earth quake loads, wind loads etc. Similarly, in bridge girders, unsymmetric loads are caused by uneven height of column, skewed girder, curved beams, irregular traffic movement etc. Unsymmetric loads usually cause bi-axial bending, which induces flexure, shear and torsion stresses that may induce unpredictable damages; carbon fibre reinforced polymer (CFRP) is being used to restrict such damages. The principal aim of this research study was to investigate the response of RC beams subjected to eccentric loads. The response was investigated in form of crack pattern, configuration & location of cracks as well as the amount of induced stresses.